mTORC1 and CK2 coordinate ternary and eIF4F complex assembly - Gandin, V.; Masvidal, L.; Cargnello, M.; Gyenis, L.; McLaughlan, S.; Cai, Y. T.; Tenkerian, C.; Morita, M.; Balanathan, P.; Jean-Jean, O.; Stambolic, V.; Trost, M.; et al. (My University, 2016)
Ternary complex (TC) and eIF4F complex assembly are the two major rate-limiting steps in translation initiation regulated by eIF2 alpha phosphorylation and the mTOR/4E-BP pathway, respectively. How TC and eIF4F assembly are coordinated, however, remains largely unknown. We show that mTOR suppresses translation of mRNAs activated under short-term stress wherein TC recycling is attenuated by eIF2 alpha phosphorylation. During acute nutrient or growth factor stimulation, mTORC1 induces eIF2 beta phosphorylation and recruitment of NCK1 to eIF2, decreases eIF2 alpha phosphorylation and bolsters TC recycling. Accordingly, eIF2 beta mediates the effect of mTORC1 on protein synthesis and proliferation. In addition, we demonstrate a formerly undocumented role for CK2 in regulation of translation initiation, whereby CK2 stimulates phosphorylation of eIF2 beta and simultaneously bolsters eIF4F complex assembly via the mTORC1/4E-BP pathway. These findings imply a previously unrecognized mode of translation regulation, whereby mTORC1 and CK2 coordinate TC and eIF4F complex assembly to stimulate cell proliferation.
Citation: Gandin, V., Masvidal, L., Cargnello, M., Gyenis, L., McLaughlan, S., Cai, Y. T., . . . Topisirovic, I. (2016). mTORC1 and CK2 coordinate ternary and eIF4F complex assembly. Nature Communications, 7, 15. doi:10.1038/ncomms11127
Additional Authors: Larose, L.;Koromilas, A. E.;Litchfield, D.;Larsson, O.;Topisirovic, I.
Keywords: Messenger-Rna Translation; Endoplasmic-Reticulum Stress; Initiation-Factor Eif2-Alpha; Unfolded Protein Response; Tumor-Suppressor Pten; Beta-Subunit